Comparación entre los métodos subjetivo y objetivo para estimar el consumo de sodio en hipertensos - Dallepiane, L. B. (2011)
Introduction: High sodium intake contributes to arterial hypertension; the relationship between high blood pressure and human aging is stronger among populations with high sodium intake. Objectives: The aim of this research is to compare subjective and objective methods on the estimate of the consumption of sodium. Methods: This is a retrospective investigation along with secondary topics from the raw data base. The subjective method used was result of the score of the application of a questionary about the sodium intake, where the sodium consumption report was converted into daily mg of sodium intake. The objective method was the result of the urine excretion of hypertensive persons older than 50 years during 24 hours. The topics were analyzed by the software SPSS using the Spearman correlation. Results: The main results did not show a significant linear correlation between the values of the sodium intake reported in the questionnaire and the values of the sodium (Na) 24 h collections. Conclusion: New studies possibly will elucidate the present results among the divergence faced with other studies.